Robust Hydrophobic and Hydrophilic Polymer Fibers Sensitized by Inorganic and Hybrid Lead Halide Perovskite Nanocrystal Emitters - Papagiorgis, Paris G.; Manoli, Andreas; Alexiou, Androniki; Karacosta, Petroula; Karagiorgis, Xenofon; Papaparaskeva, Georgia; Bernasconi, Caterina; Bodnarchuk, Maryna I.; Kovalenko, Maksym V.; Krasia-Christoforou, Theodora; Itskos, Grigorios (Frontiers in Chemistry, 2019)
Advances in the technology and processing of flexible optical materials have paved the way towards the integration of semiconductor emitters and polymers into functional light emitting fabrics. Lead halide perovskite nanocrystals appear as highly suitable optical sensitizers for such polymer fiber emitters due to their ease of fabrication, versatile solution-processing and highly efficient, tunable and narrow emission across the visible. A beneficial byproduct of the nanocrystal incorporation into the polymer matrix is that it provides a facile and low cost method to chemically and structurally stabilize the perovskite nanocrystals under ambient conditions. Herein we demonstrate two types of robust fiber composites based on electrospun hydrophobic poly(methyl methacrylate) (PMMA) or hydrophilic polyvinylpyrrolidone (PVP) fibrous membranes sensitized by green-emitting all-inorganic CsPbBr3 or hybrid organic-inorganic FAPbBr3 nanocrystals. We perform a systematic investigation on the influence of the nanocrystal-polymer relative content on the structural and optical properties of the fiber nanocomposites and we find that within a wide content range, the nanocrystals retain their narrow and high quantum yield emission upon incorporation into the polymer fibers. Quenching of the radiative recombination at the higher/lower bound of the nanocrystal:polymer mass ratio probed is discussed in terms of nanocrystal clustering/ligand desorption due to dilution effects, respectively. The nanocomposite’s optical stability over an extended exposure in air and upon immersion in water is also discussed. The studies confirm the demonstration of robust and bright polymer-fiber emitters with potential applications in backlighting for LCD displays and textile-based light emitting devices.